Feasibility Analysis of PBL Model to Build Student Creativity in Determining pH Route of Natural Indicator - Nafisah, Nafisah; Wahyu, Wawan; Sopandi, Wahyu (FKIP - Universitas Riau, 2022)
Education in the industrial era 4.0 must be adapted to the characteristics and skills of students demanded in the 21st century, one of the skills required is creativity. The data shows that the creativity of students in schools is still relatively low. Learning design must be designed to be able to build student's creativity. This study aims to analyze the feasibility of the Problem Based Learning (PBL) model to build student creativity in determining pH route of natural indicator. The method used in this research is descriptive with DbR design. DbR consists of 4 stages, problem identification and analysis, development prototype, testing and implementation, and reflection. This research was conducted only at the limited trial stage to see the feasibility of the Learning Design using the PBL model to build student creativity. The instruments used in this study were internal feasibility test sheets, external feasibility test sheets, TCOF, and creativity observation sheets. The results showed that the learning design with the PBL model is categorized as very feasible based on internal, external, and TCOF feasibility tests to develop student creativity and student creativity is categorized very well through learning using the PBL model.